Faktor Penyebab Indisipliner Siswa dalam Mematuhi Tata Tertib di Sekolah Dasar - Anzalena, Ria; Yusuf, Syahril; Lukman, Lukman (UNIB Press, 2019)
This study aimed to describe the form- student disciplinary form, factors that cause indiscipline students and how to deal with indiscipline behavior of students in keeping order in the Primary School. The approach and type of research is descriptive qualitative. Subjects were high grade students who often do indiscipline in keeping order in the Primary School. The data collection techniques through observation, interviews and documentation. Credibility test data through triangulation. The data have been analyzed through data reduction, data presentation and conclusion. The results of this research are: 1) The form of disciplinary students to comply with the rules in elementary school are most often violated is in dress, students still often do not put clothes into the violations that are not observed are meroko school environment 2) Factors that cause behavior indiscipline students in keeping order in the Elementary School that is, a) internal factors and b) external factors which consisted of factors than others, economic factors and factors of social media, every student has different factors in conducting disciplinary, 3) How to deal with indiscipline Elementary School students has been implemented through the example and habituation. Based on the results of this study concluded that the causes of indiscipline every student is different to that teachers should increase attention to the students and always carry out the recording of the students who do indiscipline so that students are more disciplined and the rules and the penalties were further optimized in accordance with the development of students.